An Empirical Investigation on the Role of exports, imports and its Determinants in Foreign Trade of Pakistan - Ali, Gulzar; Li, Zhaohua (Information Management and Business Review, 2017)
Abstract: Foreign trade was restrained by fluctuations and depreciations in currencies, nations were under financial pressure to implement protection measures in form of custom duties tariffs. These theories and thoughts have enormous impact on rules and policies of global trade throughout the world. To adopt economic liberalization and free trade zones nations all over the world are connected through number of agreements since last few centuries. In this revolutionized economic system, nations allow free trading of merchandise and services and at the same time don’t have to impose tariff in form of import and exports duties. This study attempted to empirically evaluate the role of imports, exports and its determinants in foreign trade of Pakistan applied ARDL Approach for the period of 1972-2015. The study recommends that economies with significant competitiveness and comparative advantage will be greatly benefited from export promoting policies. As far as trade partners are concerned, no considerable efforts have been done to explore new markets in direction of Pakistan’s foreign trade since its independence. The key trading partners of Pakistan in the beginning were the developed countries of West and still they are main trading partners of Pakistan.